2009
DOI: 10.1590/s1415-52732009000200005
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of Klebsiella sp. in mice fed an enteral diet containing prebiotics

Abstract: ObjectiveThis work aimed to evaluate the effect of fructooligosaccharide and inulin added to an enteral diet on the translocation of Klebsiella sp. in mice. (spleen, heart, liver, lungs, and kidneys) were aseptically collected, weighed, and analyzed for the presence of typical Klebsiella sp. colonies. Methods Four Results A higher number of CFU/g of Klebsiella was detected in the organs of the animals in the immune-suppressed group fed the diet contaminated with K. pneumoniae and without prebiotics. Animals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…For instance, FOS reduce the colonization of Salmonella enteritidis , but concomitantly increase the translocation of this invasive pathogen ( 9 , 10 ). On other hand, Silva et al ( 11 ) observed that FOS reduced Klebsiella sp. translocation.…”
Section: Introductionmentioning
confidence: 97%
“…For instance, FOS reduce the colonization of Salmonella enteritidis , but concomitantly increase the translocation of this invasive pathogen ( 9 , 10 ). On other hand, Silva et al ( 11 ) observed that FOS reduced Klebsiella sp. translocation.…”
Section: Introductionmentioning
confidence: 97%